Physical Characterization in the Fabrication of Taper Structured Fiber Optic Sensors - Parastuti, Frazna; Hikmawati, Dyah; Trilaksana, Herri (Universitas Airlangga, 2025)
In a fiber optic sensor with a taper structure, the sensor geometry is the main parameter that can affect the sensitivity of the sensor. Fiber taper fabrication is carried out using the pulling and heating method continuously and simultaneously. Based on this fabrication process, the optical fiber is pulled using an autograph until it enters the plastic deformation area. Mechanical properties analysis showed that the optical fiber had a stress of 50.24 MPa and an elastic modulus of 2.17 GPa. It was also found that the optical fiber experienced elongation up to 10.90%. The results of the digital microscope test showed that the taper process succeeded in reducing the diameter of the optical fiber by 19.77%. The optical power test shown in the form of output voltage proves that the taper process causes many evanescent waves to come out of the waveguide so that the voltage decreases up to 46.40%. Besides the ease of processing, the advantage of fabrication using this method is that the mechanical properties are measured in real-time, making this method reproducible on a mass scale.